The impact of intensive training on the morphological and functional cardiovascular adaptation of water polo and volleyball players - Plavšic, J.; Antic, M.; Jakovljevic, V. (10th International scientific conference on kinesiology. Book of abstracts, 2024)
Introduction Intense exercise over a long period leads to morphological and functional changes in the heart, cardiovascular systems, lungs, and muscles. Endurance sports produce eccentric hypertrophy of the left ventricle (LV), an increase in the dimensions of all hearts cavities, and high fitness expressed in maximum oxygen consumption (VO2max), while strength sports lead to concentric hypertrophy of the LV without a significant increase in heart dimensions with a small increase in aerobic capacity compared to sedentary people.